ANALISIS SPASIAL TEMPAT PEMBUANGAN SAMPAH SEMENTARA (TPS) DI KOTA JAMBI - Silvi Herwindah; Triyatno Triyatno; yurni suasti (JURNAL BUANA, 2020)
The purpose of this research is 1) determine the suitability location of TPS. 2) determine the scope of TPS services to the settlement. 3) determine the capacity of TPS. This type of research is descriptive quantitative. 1) Several parameters used in the model of Geographic Information System with scorring method to find out the suitable of TPS location. 2) Service area analyst method to find out the scope of TPS services. 3) Comparing between volume of refuse and TPS to find out the capacity of TPS, next used formulation of CP (Container Procurement) the number of containers that need to be added. The result of this research are 1) All TPS in Jambi were appropriate class. 2) The result service area analyst showed that scope of TPS services to the settlement in Jambi city not enough, where 57,27% of the population served optimally. 3) The capacity of TPS in Jambi city still need the number of containers, that were 30 unit.